Physicochemical Characterisation of Water and Sediment of the Semimechanized Artisanal Gold Mining Environment of the Béké Locality - Blanche Mefomdjo Fotie; Harouna Boukari; Ibrahim Elhadji Daou; Christian Kapta Momegni; Manyi Audrey Ebua Eta; Louis Bernard Tchuikoua; Luc Leroy Mambou Ngueyep (Applied and Environmental Soil Science)
This paper aims to investigate the level of pollution of water, sediment, and soil due to semimechanized artisanal gold mining in Béké, Adamawa region of Cameroon. For this purpose, water and sediment samples were collected and analyzed. In order to achieve this goal, several research studies and field observations were carried out. Questionnaires were also used to complement field investigations. All these enabled the identification of the potential sources of impacts on the human, physical, and biological environment. Three soil samples (S1, S5, and S7) were collected on the same spot with the water sample and analyzed to assess the intensity of soil contamination. The water samples (W1–S9) were characterized physically, chemically, and microbiologically to evaluate the water quality contamination. The results of the physicochemical analysis of the water samples showed that the rivers in this zone are moderately acidic (with pH values ranging from 5.11 to 6.37) and slightly mineralized (with sample W2 collected from the Béké river having an iron concentration of 6.7 g/L). The pattern of mean trace metal concentration in sediments was Fe > Mn > Cr > Pb > Cu > Zn. According to pollution indices, the contamination degree (CD) varied from 4.03 to 4.56 corresponding to low contamination. The index of ecological risk (Eri) for all the trace metals was low (Eri ≤ 40) and the geoaccumulation index (Igeo) ranged between uncontaminated and moderately contaminated (Igeo 0-1). The result of our field investigations and analysis shows that the semimechanized artisanal gold mining in the locality of Béké has very significant environmental consequences such as land degradation, deforestation, water pollution, and landscape modification.